Study on the influence of boundary conditions on the airflow resistivity measurement of porous material. (April 2020) - Xiong, Xinzhong; Liu, Xuewen; Wu, Liang; Pang, Jinxiang; Zhang, Hewei
Abstract: Acoustic parameter measurement of porous materials is critical to the simulation of sound absorption. In all parameters of the material the airflow resistivity measurement is greatly affected by the environment and boundary conditions, so the result is unstable. The influence of different boundary conditions on the measurement of polyurethane's airflow resistivity is studied in this paper. Airflow resistivity is measured under different boundary conditions. To verify the test results, the porosity also was measured and the tortuosity and characteristic lengths were calculated in the software by using appropriate acoustic model. The sound absorption coefficient is obtained by AMDesigner (AMDesigner, which is a commercial software about porous materials simulation developed by Jinxiang Pang) after inputting all above material parameters. Comparing the absorption coefficient measured by experiment with that obtained by simulation. It shows that after using petroleum jelly sound absorption simulated by AMDesigner is agreement well with the measurement value in the whole frequency band. When add two rings sound absorption by simulation and test match well under low-frequency region. While directly measuring the airflow resistivity after cutting, the results from test and simulation just get poorly agreement. The conclusion from the paper could provide more experiences for airflow resistivity measurement of porous foam material.